Editorial Advisory Board Memeber - Zarkada, Anna K. (My University, 2026)
he EAB comprises experts who provide guidance on a journal's development, including its editorial scope, focus, and the appointment of new board members. They also assist in selecting outstanding papers and act as reviewers when necessary.